2020
DOI: 10.1038/s41598-020-74233-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the association between polymorphisms of PRM1 and PRM2 and the risk of male infertility: a systematic review, meta-analysis, and meta-regression

Abstract: Studies have reported the genetic gives rise to male infertility. The aim of the present meta-analysis was to evaluate the association between PRM1 (rs737008 and rs2301365) and PRM2 (rs1646022 and rs2070923) polymorphisms and susceptibility to male infertility. The association between PRM1 and PRM2 polymorphisms and the risk of male infertility was evaluated using specific search terms in the Web of Science, Cochrane Library, PubMed, and Scopus databases without language restriction until January 28, 2020. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Previous studies reported different negative impacts due to a low gene or protein expression of PRM on male fertility, causing the decline in semen quality [25][26][27][28][29]. Consistently, clinical studies in humans showed the association of PRM with male infertility cases [30]. Dogan et al [13] reported the protein of PRM1 reduction in LF bulls, also characterized by an increase in DNA fragmentation.…”
Section: Introductionmentioning
confidence: 75%
“…Previous studies reported different negative impacts due to a low gene or protein expression of PRM on male fertility, causing the decline in semen quality [25][26][27][28][29]. Consistently, clinical studies in humans showed the association of PRM with male infertility cases [30]. Dogan et al [13] reported the protein of PRM1 reduction in LF bulls, also characterized by an increase in DNA fragmentation.…”
Section: Introductionmentioning
confidence: 75%
“…In order to indicate the underlying causes, extensive research has been done on the genetic reasons of male infertility in recent years. A number of polymorphisms that have a fundamental role in sperm chromatin density and spermatogenesis have been empirically discovered [ 23 ]. The results of the RPM can serve as a basis for further prospective studies of the molecular genetic mechanisms of pathogenesis of reproductive diseases, determining the prognosis of treatment efficacy, and developing new approaches to personalized treatment of genetic disorders leading to infertility.…”
Section: Discussionmentioning
confidence: 99%
“…A statistically significant increase in NBT (+) cells was obtained in COVID-19 induces respiratory-predominant multiorgan dysfunction, including myocardial, renal, enteric and hepatic dysfunction, which coincides with the tissue expression of ACE2. 3 Meanwhile, several studies have shown that ACE2 is expressed in human testes (eg spermatogonia, Leydig cells and Sertoli cells), 4,5 suggesting that the testes may be another organ affected by COVID-19.…”
Section: Sperm Preparation Techniques and Oxidative Stress Levelsmentioning
confidence: 99%